2016
DOI: 10.12740/pp/45218
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disturbances as a first clinical symptom of Wilson’s disease – case report.

Abstract: WD should be always considered in differential diagnosis of psychiatric disorders in young patients, especially if they present additional extrapyramidal or hepatic symptoms. It is also extremely important to remain cautious when drugs with high affinity to dopamine D2 receptors need to be initiated in patients already diagnosed with WD, as they may result in severe and often irreversible neurological complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The psychiatric symptoms of WD are highly prevalent and among the biggest challenges in WD management for several reasons. 4 , 27 , 55 , 57 , 67 , 68 First, because the early diagnosis of WD in patients with initial psychiatric symptoms is difficult; 12 , 13 , 70 , 75 and second, because there are no guidelines for the treatment of psychiatric symptoms in WD that take the specificity of this disorder into account. 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The psychiatric symptoms of WD are highly prevalent and among the biggest challenges in WD management for several reasons. 4 , 27 , 55 , 57 , 67 , 68 First, because the early diagnosis of WD in patients with initial psychiatric symptoms is difficult; 12 , 13 , 70 , 75 and second, because there are no guidelines for the treatment of psychiatric symptoms in WD that take the specificity of this disorder into account. 1 …”
Section: Discussionmentioning
confidence: 99%
“…In summary, there is a wide spectrum of psychiatric symptoms observed in WD, leading to the conclusion that WD should be included in differential diagnosis, especially in young adults presenting with the first episode of psychiatric symptoms, 12 and WD should be suspected in all young adult psychiatric patients presenting with extrapyramidal and/or hepatic symptoms. 12 , 13 , 62 …”
Section: Psychiatric Symptoms Of Wdmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric symptoms/disorder Occurrence/topic Ala et al (2005) depression onset Ara ujo-de-Freitas et al 2014depression onset Aravind et al (2009) mania onset Bidaki et al (2012) psychosis onset Carr and McDonnell (1986) adjustment disorder onset Chakraborty et al (2015) depression onset Chan et al (2005) depression/personality disorder/suicide attempt onset Chand and Murthy (2006) mania onset Crumley (1990) depression onset Davis and Borde (1993) catatonia onset Grover et al 2014psychosis treatment Juki c et al 2006psychosis onset Keller et al (1999) mania onset Kenar and Menteseoglu (2014) mania in course Kontaxakis et al (1988) psychosis onset Krishnakumar and Riyaz (2005) depression onset Krsti c et al 2014psychosis onset Kulaksizoglu and Polat (2003) mania treatment Kumawat et al (2008) obsessive-compulsive disorder onset Leggio et al (2007) anxiety in course Lin et al (2006) Attention Deficit Hyperactivity Disorder (ADHD) onset Lingam et al (1987) conduct disorder onset Litwin, Chabik, and Członkowska (2013) depression treatment Litwin et al (2016) mania treatment Loganathan et al (2008) mania in course Machado et al (2008) mania onset Matarazzo (2002) psychosis onset McDonald and Lake (1995) psychosis treatment McDonnell and Esmonde (1999) bipolar disorder onset Millard et al (2015) irritability/suicidal ideation onset Mitra et al (2014) mania in course Modai et al (1985) schizophrenia-like psychosis treatment M€ uller (1999) psychosis/change in mood/aggressive behaviour/suicide attempt onset Nayak et al 2012catatonia onset Nazariah et al 2011mania onset Negro and Louz a Neto (1995) depr...…”
Section: Referencesmentioning
confidence: 99%
“…Moreover, lithium might worsen tremor and impair cognition, and copper chelation therapy has only been shown to reduce manic symptoms (Loganathan et al, 2008;Machado et al, 2008;Mitra et al, 2014). Some authors reported a good response of manic symptoms with atypical antipsychotics, such as olanzapine (Litwin, Dzie_ zyc, Karli nski, Szafra nski, & Członkowska, 2016), and quetiapine (Kulaksizoglu & Polat, 2003;Zimbrean & Schilsky, 2015). Traditional neuroleptics, such as haloperidol, could determine the occurrence of extrapyramidal symptoms in individuals both with BD (Varghese et al, 2008) and with psychotic symptoms in WD (Nayak et al, 2012).…”
Section: The Use Of Psychotropic Medications For Psychiatric Symptomsmentioning
confidence: 99%